2019
DOI: 10.18502/kss.v3i17.4668
|View full text |Cite
|
Sign up to set email alerts
|

SEFT Based Individual Counseling to Reduce the Academic Anxiety

Abstract: The results showed that the level of academic anxiety experienced by junior high school students in the Province of Special District of Yogyakarta can be categorized as moderate. It was also revealed that Guidance and Counseling teachers also have been doing something in reducing these problems by providing counseling either individually or in groups to their students and using a variety of appropriate approaches and techniques, though it was not maximized. Based on these results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These 30 children had different levels of anxiety, 46% experienced moderate anxiety, 17% experienced severe anxiety, and 17% did not experience anxiety. Based on the test results, this research found that there was an effect of SEFT therapy on reducing students' anxiety levels (Purwanti & Munawaroh, 2019).…”
Section: Transpersonal Psychology Practice On Cases Anxiety In a Reli...mentioning
confidence: 93%
“…These 30 children had different levels of anxiety, 46% experienced moderate anxiety, 17% experienced severe anxiety, and 17% did not experience anxiety. Based on the test results, this research found that there was an effect of SEFT therapy on reducing students' anxiety levels (Purwanti & Munawaroh, 2019).…”
Section: Transpersonal Psychology Practice On Cases Anxiety In a Reli...mentioning
confidence: 93%